2013
DOI: 10.1037/a0031637
|View full text |Cite
|
Sign up to set email alerts
|

Don’t interrupt me! An examination of the relationship between intrusions at work and employee strain.

Abstract: Interruptions by others, or intrusions, are a common phenomenon in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 40 publications
4
80
1
2
Order By: Relevance
“…The first is a single item within the Organizational Constraints Scale (OCS; Spector & Jex, ). This item specifically assesses the frequency with which “you find it difficult or impossible to do your job because of interruptions by other people.” The second attempt is a four‐item scale assessing intrusions (Lin et al, ). In addition to providing a more comprehensive measure of all interruption dimensions, our measure differs from previous work in several ways.…”
Section: Current Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The first is a single item within the Organizational Constraints Scale (OCS; Spector & Jex, ). This item specifically assesses the frequency with which “you find it difficult or impossible to do your job because of interruptions by other people.” The second attempt is a four‐item scale assessing intrusions (Lin et al, ). In addition to providing a more comprehensive measure of all interruption dimensions, our measure differs from previous work in several ways.…”
Section: Current Researchmentioning
confidence: 99%
“…Specifically, Study 3 explored the construct validity and incremental validity of the WIM with workplace stressors and strains to understand whether the WIM subscales differentially predict stressors and strains in a new sample of employees. Study 3 also included a previously existing measure of intrusions (Lin et al, ) to examine convergent validity with the WIM‐intrusions subscale.…”
Section: Study 3: the Wim In A Sample Of University Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists a vast body of literature that has studied the trade off between disruption and awareness caused by notifications [4,3,1,2]. However these works primarily focused on workplace environments where the user is engaged with some computational task at hand and notifications are delivered to the desktop computer.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have shown that it requires 25 minutes to resume a primary task after an interruption [4] affecting work quality [5]. Repeated interruptions also increase anxiety, exhaustion, and annoyance [6].…”
Section: Introductionmentioning
confidence: 99%